Prediction of Fracture Opening Pressure in a Reservoir Based on Finite Element Numerical Simulation: A Case Study of the Second Member of the Lower Triassic Jialingjiang Formation in Puguang Area, Sichuan Basin, China - Li, Jian; Zu, Kewei; Li, Qi; Zeng, Daqian; Li, Zhongchao; Zhang, Jixi; Luo, Zhouliang; Yin, Nanxin; Zhu, Zhenjun; Ding, Xiaojun (Frontiers in Earth Science, 2022)
All stages of oil and gas exploration and development involve the study of in-situ stress. Since the traditional two-dimensional and three-dimensional homogeneous models can no longer fulfil the requirements of research and production, numerical simulation of the stress field has become an effective study method. In this study, we took the Jia 2 member in Puguang area as a case to establish a geological model and a mechanical model based on the tectonic framework and the distribution characteristics of the rock mechanical parameters, respectively, and loaded the model with the present-day in-situ stress state calculated from the logging data as the boundary conditions. The simulation results show that (1) the orientation of the maximum horizontal principal stress in the study area is near E-W, and the in-situ stress orientation is locally deflected due to the influence of faults; and (2) the magnitude of in-situ stress is predominantly affected by the burial depth and lithology, and the minimum horizontal principal stress, maximum horizontal principal stress, and differential stress are mainly concentrated in the ranges of 30-60, 50-80, and 10-40 MPa, respectively. We also analysed the opening sequence of the multiple fracture systems during development, using the present-day stress field model. The analysis revealed that the E-W fractures will open first, and the continuously increasing operating pressure will lead to formation breakdown, producing a fracture network.